Corporate social responsibility and football clubs: The value of environmental sustainability as a basis for the rebranding of Real Betis Balompié in Spain - Lobillo-Mora, Gema María; Ginesta-Portet, Xavier; De San Eugenio Vela, Jordi (MDPI AG, 2021)
On October 2020, Real Betis Balompié, a football club located in Seville (Andalucia), presented the Forever Green programme, a global programme of Corporate Social Responsibility (CSR) that, through the club’s foundation, enables the entity to position itself in areas of sustainable development and environment at a global level. This project was preceded by a sponsorship initiative with the Green Earth project, as well as having been the first football club to sign the United Nations’ Climate Change Now initiative. This article aims to explain the rebranding process of a sports brand based on values linked to sustainability and to assess the impact this rebranding process has had on the fans’ perception of the brand. The methodology used was a combination of in-depth interviews with the executives charged with leading the rebranding process and a convenience survey given to 100 fans to assess the impact of the initiative. The results show that both the entity and the fans agree on a holistic vision of what the CSR is, altruistic in nature, and that its initiatives should be applicable across the entire organisation. However, although the club’s link with values of the environment and sustainability is highly valued by the fans, they still do not feel directly called upon to take part in actions that the club organises.
Keywords: Desarrollo sostenible; Fútbol - Aspectos ambientales; Real Betis Balompié; LaLiga; Corporate social responsibility; Sustainability; Environment